1995
DOI: 10.1093/glycob/5.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of glycan moieties of lipid intermediates leads to a single Man5GlcNAc oligosaccharide isomer: a study with permeabilized CHO cells

Abstract: This paper presents kinetic and structural analyses of oligosaccharide material released during glycosylation in permeabilized Chinese hamster ovary cells incubated with sugar nucleotides. Permeabilized cells released 30 times more oligosaccharide material than metabolically labelled cells, normalized to the amount of labelled glycoprotein acceptor, making this an amenable system for study. Fifteen to forty per cent of the oligosaccharide material released by permeabilized cells was oligosaccharide-phosphate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 0 publications
2
51
0
1
Order By: Relevance
“…The size of these oligosaccharides also closely resembles that of those derived from protein-bound oligosaccharides (shown in Fig. 1), and they are most likely cleaved from protein or LLO as reported by others (34)(35)(36)(37)(38)(39)(40).…”
Section: Fractionation and Analysis Of [ 3 H]mannose-labeled Productssupporting
confidence: 79%
“…The size of these oligosaccharides also closely resembles that of those derived from protein-bound oligosaccharides (shown in Fig. 1), and they are most likely cleaved from protein or LLO as reported by others (34)(35)(36)(37)(38)(39)(40).…”
Section: Fractionation and Analysis Of [ 3 H]mannose-labeled Productssupporting
confidence: 79%
“…Although the sequential processing events of free OSs have been well characterized (15)(16)(17)(18)(19), the molecular nature of the enzyme͞transporters involved in this process has not been identified, with the exception of cytosolic PNGase (35). Because free OSs in the lumen of the ER can potentially interfere with the glycan-dependent protein quality control system in the ER (2-4), the rapid clearance of them from the lumen of the ER may be of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that, during the N-glycosylation of proteins in the ER, a significant number of unconjugated, free oligosaccharides (free OSs) are formed (7)(8)(9). The occurrence of free OSs has been reported in a wide variety of cells (10)(11)(12)(13)(14), and their sequential processing event of free OSs in mammalian cells has also been well characterized (15)(16)(17)(18)(19). When the free OSs are formed in the lumen of the ER, they are transported out of the ER to the cytosol (15).…”
mentioning
confidence: 99%
“…Free oligosaccharides (fOS) have also been described in mammalian cells, yeast, plants, and fish (11). In these cases, fOS are released from N-linked glycoproteins by peptide-N-glycanase (PNGase) within the endoplasmic reticulum associated protein degradation pathway (12) or from dolichol-pyrophosphate-linked oligosaccharides (Dol-PP-OS) by a pyrophosphatase that generates phosphorylated free oligosaccharides (fOS-P) (13,14). Other studies have suggested that in the absence of a sufficient acceptor, OS are transferred from their Dol-PP carrier to water within the ER (15,16).…”
mentioning
confidence: 99%